Reflexões à margem de um tema: geografia e turismo no Brasil - Tulik, Olga (Anais do Museu Paulista: História e Cultura Material, 1981)
The development of a teaching program as a fulfilment of a tourism course of the “Escola de Comunicações e Artes” (School of Communication and Arts) of the University of São Paulo has resulted in some considerations which are put forth here. These teaching lectures were carried up through a cooperation of the Section of Geography of the “Museu Paulista” (Paulista Museum) to the “Escola de Comunicações e Artes”. The tourism activities and their impact on the Brazilian landscape were described as a geographer sees them.